Enhancing learning outcomes through problem-based learning in plant reproduction topics - Nurhuda, Nurhuda; Panjaitan, Ruqiah Ganda Putri; Wartiningsih, Wartiningsih (IKIP PGRI Pontianak, 2024)
This study aims to enhance students' learning outcomes on the topic of plant reproduction in 9th-grade classes through the application of the Problem-Based Learning (PBL) model. This study used a Classroom Action Research (CAR) methodology with two learning cycles to improve student learning outcomes on the topic of plant reproduction in 9th grade. In the first cycle, the average learning outcome score was 72, which is below the minimum mastery criterion (<75). Observations were made by an observer regarding the students' learning activities and the teaching process conducted by the teacher during the first cycle. These observations served as a reference for the subsequent learning cycle. In the second cycle, there was an improvement in learning outcomes, with an average score of 85, indicating that students, on average, had achieved the minimum mastery criterion (minimum mastery score 75). The classroom action research involved four stages: planning, implementation, observation, and reflection. The results show that the gradual application of the PBL model progressively improved students' learning outcomes on the topic of plant reproduction.